An assessment of socio-cultural challenges of social distancing as a means of COVID-19 control in Lagos state, Nigeria - Charles-Eromosele, Titilope O.; Maduafokwa, Blossom A.; Kanma-Okafor, Oluchi J.; Oluwole, Esther O.; Oridota, Ezekiel S.; Giwa, Opeyemi O.; Ibenye-Ugbala, Chioma J.; Abdulkareem, Aisha T.; Pitan, Adesola A.; Matti, Oluwadamilola A.; Onajole, Adebayo T. (International Journal Of Community Medicine And Public Health, 2024)
Background: There are attendant socio-cultural challenges of social distancing in controlling COVID-19 in developing countries which must be overcome. The objectives of this study was to assess knowledge, attitude and practice on social distancing, to determine the socio-cultural challenges and assess the coping mechanisms to the socio-cultural challenges of social distancing as a means of COVID-19 control in Lagos state, Nigeria. Methods: This was a cross-sectional descriptive study that assessed the socio-cultural challenges of social distancing as a means of COVID-19 control in Lagos state, Nigeria. The study population included adults ≥18 years that have resided in Lagos state for more than six months. Respondents were recruited through the internet, using the social media platforms. A total of 500 responses were analysed. Quantitative analysis was done using IBM SPSS version 22. Results: Overall, about 98.2% of the participants had adequate knowledge of social distancing as a means of COVID-19 control, 51% of the participants had positive attitude towards social distancing as a means of COVID-19 control, and about 98.2% of the participants practised social distancing. About a quarter (27.2%) saw social distancing as a violation of human right and 97% agreed that it affected education in schools. Internet-based communication, teleworking, financial compensation, support groups, health education and special attention to the vulnerable were indicated coping strategies. Conclusions: The findings showed significant socio-cultural challenges in implementing COVID-19 mitigating measures such as social distancing and recommended mass health education plus a good socio-economic support system will help promote the adoption of preventative guidelines.